2011
DOI: 10.1111/j.1365-2109.2011.02804.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and fish culture in Patagonia: present situation and perspectives

Abstract: Temperature increment is one of the most visible aspects of climate change. Reservoirs in northern Patagonia are the main location for rainbow trout cage aquaculture activities in Argentina and here, surface water temperature shows an increment that despite leading towards better growth rates, also provokes lack of ovulation, atresia and a partial or total absence of spawning during the breeding season. During the early life history, low survival rates at hatching and first feeding are also observed. The incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Besides, a few mature oocytes were found in the G2 group, and in some of them, it was possible to observe in the animal pole the presence of a micropylar apparatus, as described by Drummond et al (2000) to Astyanax bimaculatus lacustris. Changes in the development of oocytes that lead to the process of atresia may be associated with stressful situations as inadequate management (Scherek et al, 2001), food restriction (Corriero et al, 2011), exposure to toxic substances (Gaber et al, 2013;Magar & Bias, 2013;Narayanaswamy & Mohan, 2014), and also conditions of hours of light and water temperature that are unfavorable to maturation and spawning (Linares-Casenave et al, 2002;Migaud et al, 2003;Báez et al, 2011). The last two factors may have resulted in the high incidence of atretic follicles in the G1 group and were probably responsible for the interruption of vitellogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a few mature oocytes were found in the G2 group, and in some of them, it was possible to observe in the animal pole the presence of a micropylar apparatus, as described by Drummond et al (2000) to Astyanax bimaculatus lacustris. Changes in the development of oocytes that lead to the process of atresia may be associated with stressful situations as inadequate management (Scherek et al, 2001), food restriction (Corriero et al, 2011), exposure to toxic substances (Gaber et al, 2013;Magar & Bias, 2013;Narayanaswamy & Mohan, 2014), and also conditions of hours of light and water temperature that are unfavorable to maturation and spawning (Linares-Casenave et al, 2002;Migaud et al, 2003;Báez et al, 2011). The last two factors may have resulted in the high incidence of atretic follicles in the G1 group and were probably responsible for the interruption of vitellogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier surveys show that some of the montane lakes we sampled probably lacked suitable spawning habitat to support reproduction by introduced fish (Anderson & Donald, 1980). These warmer water temperatures, along with low levels of dissolved oxygen, can cause salmonids to experience a wide range of complications in their reproduction, feeding behaviour, movement and survival (Baez, Aigo & Cussac, 2011), which could ultimately result in extirpation of stocked fish in montane systems. Further, Todd et al (2008) showed that mortality can occur when mountain salmonids are exposed to water temperatures near 22°C, or chronically exposed to temperatures near 17.5°C.…”
Section: Discussionmentioning
confidence: 99%
“…Mean midsummer water temperatures above 17°C were often recorded in warmer montane lakes in our study. These warmer water temperatures, along with low levels of dissolved oxygen, can cause salmonids to experience a wide range of complications in their reproduction, feeding behaviour, movement and survival (Baez, Aigo & Cussac, 2011), which could ultimately result in extirpation of stocked fish in montane systems. Further, since lower montane lakes are typically more easily accessibile to anglers, angling pressure may play an important role in eliminating fish from these lakes more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…() found that low winter temperatures may currently restrict C. carpio . Present capture data for the Negro River show water temperatures below preference and optimum growth, but climate warming could help future southward advances in the area (Aigo et al ., , ; Cussac et al ., ; Báez et al ., ). In particular, it should be considered that the present analysis is based on 1961–1990 mean values and that these temperatures have increased in the intervening years by between 0·5 and 1·5° C in Patagonia (http://www.smn.gov.ar/serviciosclimaticos/?mod=cambioclim&id=1).…”
Section: Discussionmentioning
confidence: 97%